11 Quality improvement project for out-of-hours clinical handover. (12th November 2018) - Krishnan, Deepa Bagepalli; Nixon, Neil
Abstract : Aim: Nottinghamshire Healthcare NHS Foundation Trust (NHFT) provides a variety of mental health services across Nottinghamshire. During out-of-hours work, junior doctors cover each of these three main hospital sites. The Health Education East Midlands (HEE) Quality Management visit concluded the handover system in NHFT was not fit for purpose, posing significant risks to both patients and junior doctors. The aim of our quality improvement project was to assess these concerns using a mixed methodology, including local surveys and audit; and secondly to make any necessary quality improvements to the handover process and guidance. The pre-implementation evaluation of the handover system in use consisted of a survey and an audit. Methods: The quality improvement strategy involved a two-pronged approach, which included the development of a new IT-based handover recording tool and improving education and training in its use. We used Plan-Do-Study-Act (PDSA) cycles between August 2015 and August 2016 to implement changes. Phase 2 of the project involved audit, education and training to consolidate and reinforce the change to make it sustainable through creation of a white board animation video for junior doctors. Results: Percentage of recorded handovers was the main outcome measure. Quality outcomes improved after the phase 1 and were sustained during the phase 2 of the project due to introduction of mandatory recording fields. Conclusion: We learnt that the active engagement of end users in the designing and implementation of the new IT handover system was a key factor in optimal development. We learnt that continuous induction, training and monitoring are important to sustain high usage of the system. Also, use of project management tools from the start will improve efficiency and time management. This project demonstrates how existing resources within a NHS Trust can be collaboratively and iteratively deployed to improve patient care.